2018
DOI: 10.2196/games.8609
|View full text |Cite
|
Sign up to set email alerts
|

Gamified Cognitive Control Training for Remitted Depressed Individuals: User Requirements Analysis

Abstract: BackgroundThe high incidence and relapse rates of major depressive disorder demand novel treatment options. Standard treatments (psychotherapy, medication) usually do not target cognitive control impairments, although these seem to play a crucial role in achieving stable remission. The urgent need for treatment combined with poor availability of adequate psychological interventions has instigated a shift toward internet interventions. Numerous computerized programs have been developed that can be presented onl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Currently, the literature on CCT as treatment augmentation, especially in anxious samples, is limited (Course-Choi et al, 2017). On top of the promising findings in the context of depression (Koster et al, 2017), CCT also holds potential from an implementation point-of-view, as it could be incorporated into existing programs through a dedicated online platform, that has been developed taking into account the needs of patients and clinicians (Vervaeke et al, 2018). However, our results suggest that the contribution of CCT over ACT in an anxious sample is limited when combined with a fear of failure training.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the literature on CCT as treatment augmentation, especially in anxious samples, is limited (Course-Choi et al, 2017). On top of the promising findings in the context of depression (Koster et al, 2017), CCT also holds potential from an implementation point-of-view, as it could be incorporated into existing programs through a dedicated online platform, that has been developed taking into account the needs of patients and clinicians (Vervaeke et al, 2018). However, our results suggest that the contribution of CCT over ACT in an anxious sample is limited when combined with a fear of failure training.…”
Section: Discussionmentioning
confidence: 99%
“…Upon completion of the full training procedure (10 sessions), all grid cells were unlocked. Input regarding gamification was collected in a previous stage taking into account the needs and concerns of the users (for a thorough discussion, we refer to Vervaeke et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the current study is to examine the impact of gamification on user experience, cognitive transfer, and emotional transfer following adaptive PASAT training. A cognitive control training platform was developed based on a focus group with remitted depressed patients (Vervaeke et al 2018). Before testing this platform using a clinical sample, it is undergoing several development steps, to test essential features for usability in interventional research, following an experimental medicine approach (Riddle and Science of Behaviour Change Working Group 2015).…”
Section: Aim Of the Studymentioning
confidence: 99%
“…Although multiple efforts have been made to prevent drop-out from online administered cognitive training procedures (e.g., using psychoeducation and gamification techniques, based on focus groups with end users; Vervaeke et al, 2018 , Vervaeke et al, 2020 ), relatively few studies have examined predictors of adherence to online CCT interventions targeting RNT or mood- and anxiety symptoms. Using a fully app-based eHealth intervention, Arean et al (2016) found higher baseline depressive- and anxiety symptoms to be associated with less use of online CCT in a sample with mild to moderate depressive symptomatology.…”
Section: Introductionmentioning
confidence: 99%